Pathologically Tumor-free Resection Margin Distance as a Surrogate Parameter in Primary Vulvar Squamous Cell Cancer: Analysis of a Large Two-Center Patient Cohort - Balog, Eva; Stuebs, Frederik A.; Berndt, Ronald; Dietl, Anna K.; Geppert, Carol; Hartmann, Arndt; Thunich, Oliver; Beckmann, Matthias W.; Koch, Martin C. (Geburtshilfe und Frauenheilkunde, 2025)
This study evaluated the role of tumor-free margin distances and other prognostic factors, including age, lymph-node metastases, lymphatic vessel invasion, and local recurrence, on the survival of patients with vulvar squamous cell carcinoma (VSCC) undergoing primary surgical treatment.A retrospective analysis reviewed the records of 232 VSCC patients who had undergone primary radical local excision with R0 resection between 2009 and 2021 at ANregiomed Hospital Ansbach and Erlangen University Hospital (Germany). Patients, aged 18 and older with no distant metastases, were grouped by resection margin distances (1 to ≤ 3 mm, 3 to ≤ 8 mm, > 8 mm) for survival analysis using the Kaplan–Meier and log-rank tests. A Cox proportional hazards regression model incorporating multiple covariates, selected using the best-subset selection method and guided by the Akaike information criterion (AIC), was used. In the next step, we conducted a separate analysis of the patients who experienced a local recurrence.The median age of the 232 patients analyzed was 69 years, with a median follow-up period of 10.5 years; 82 patients died. Survival varied significantly relative to resection margin distance (p = 0.0022), with the highest rates in the 1 to ≤ 3 mm group and the lowest in the > 8 mm group. Multivariate analysis revealed that age, lymphatic vessel invasion, and resection margin distance significantly influenced survival, with higher values associated with increased mortality. Out of 232 patients analyzed, 43 developed a local recurrence. In the group with resection margins of 1 to ≤ 3 mm, 37% of patients experienced a local recurrence. Among those with margins of 3 to ≤ 8 mm, 44% had a recurrence, while only 19% of patients with margins > 8 mm showed a local recurrence.The study underscored the significance of tumor-free margin distance as a surrogate marker for survival in VSCC patients. In addition to lymphatic vessel invasion as the most critical prognostic factor, tumor-free resection margin distance and age emerged as significant predictors of overall survival. The findings advocate for tailored, function-preserving surgical approaches to improve patient outcomes.
Keywords: vulvar cancer; squamous cell cancer; resection margins